Influence of barley grain treated with alkaline compounds or organic extracts on ex vivo site and extent of digestion of starch - Naseroleslami, Reza (Asian-Australasian journal of animal sciences, 2018)
OBJECTIVE: Two ex vivo experiments were conducted to verify the effect of barley grain (Nusrat cultivar) treated with alkaline compounds (AC) including alum, ammonium, and sodium hydroxide or cation-exchanged organic extracts (OE) prepared from alfalfa hay, sugar beet pulp and Ulva Fasciata, on extent and digestion of starch